Artificial Intelligence (AI) to Support Curriculum Development for English Language Teaching in South Sulawesi's Secondary Schools - Andi Asrifan (JEELS (Journal of English Education and Linguistics Studies), 2025)
The swift advancement of Artificial Intelligence (AI) presents novel prospects for improving English Language Teaching (ELT) curriculum design. Although AI has been extensively researched in high-resource environments, there is a paucity of studies addressing its implementation in areas with infrastructural and training deficiencies, such as South Sulawesi, Indonesia. This study sought to examine stakeholders' awareness of AI, their views on its advantages and obstacles, and its prospective function in the creation of ELT curricula. Utilizing a mixed-methods approach, data were gathered from 178 individuals (100 students, 60 teachers, and 18 administrators) via structured questionnaires and semi-structured interviews. Quantitative data were examined by descriptive and correlational statistics, whereas qualitative data were subjected to theme analysis. Results demonstrate a moderate overall awareness of AI, accompanied by a robust acknowledgment of its promise for individualized learning, engagement, and adaptive content delivery. Nonetheless, obstacles such as inadequate teacher training, poor infrastructure, and low digital preparedness continue to exist. Correlation research indicated a substantial positive association between AI familiarity and perceived advantages. The report advocates for focused professional development, strategic resource allocation, and the incorporation of AI competencies into national curriculum frameworks. These findings advance AI-in-education research by providing context-specific insights for the implementation of AI-enhanced English language teaching curricula in resource-diverse environments.